The Majan family and their role in public life in Baghdad until the end of the late Abbasid era (656 AH / 1258 CE) - ., Nawal Nazem (Al-Adab Journal, 2015)
Islam Religion had been raised in India through Islamic conquests, the first conquest was done by the leader MOHAMMED IBN ALKASIM ALTHKAFI, which included sind and most cities had failed under controlling Muslims, then the Ialam settled down in India and the first state which was raised the ALGHZNAWIA state who founded it the sultan Mahmud Al Ghazni 392 AH/1001 AC and his conquests in India, this state had been continue until the coming of the ruling other families, the people lived in grace and security. The last family who ruled India was Mongols that stating for three centuries. There is point of view that I didn’t mentioned in my humble thesis any thing about the town, unless the little which was written by the historian or explorers. It is town which had raised by Islam later in the age of the sultan SABKTAKEEN 351H/582AC and his son MAHMOUD 421H/1031AC. It seems that the Islam had settle down well in this town and it born most of the scientists and scholars. We mean this town is LAGHMAN, while the information is lack about that town, however there are evidence for appearing that family and also appeared in Baghdad wee appeared original family that got important jobs and ranks and judges religious men teachers and most of them believed in HANAFI dogma, the economic and social condition of that town are poor and not clear.